Preparation method and application of metal zinc negative electrode protection layer of aqueous zinc ion battery

By using high-temperature calcination in aqueous zinc ion batteries as zinc negative electrode protective layer, a porous structure is formed, which solves the problems of uneven deposition of zinc ions and dendrites and significantly improves the cycle stability and electrochemistry of the battery performance.

CN119218943APending Publication Date: 2024-12-31ANYANG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411411818.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-26
Filing Date
2024-10-11
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the charging and discharging process of aqueous zinc ion batteries, zinc ions are unevenly deposited to form dendrites, which consumes active materials, resulting in reduced Coulomb efficiency and short-circuiting of the battery, and the hydrogen evolution reaction increases internal pressure, hindering its commercialization process.

Method used

Using a preparation method for metal zinc negative electrode protective layer of aqueous zinc ion battery, by grinding zinc powder and urea at room temperature, and then heating it to 500-600°C in a tube furnace, h-g-C3N4 material is obtained as the protective layer, and by Ultrasonic coated on zinc foil and dried in vacuo to form a porous structure with a high specific surface area to inhibit dendritic growth.

Benefits of technology

This method effectively inhibits uneven deposition of zinc ions, prevents dendrites from punctured by the separator, significantly improves the cycle stability and electrochemical performance of the battery, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218943A_ABST
    Figure CN119218943A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical energy storage devices, and particularly relates to a preparation method of a metal zinc negative electrode protective layer of an aqueous zinc ion battery, which comprises the following steps: (1) mixing zinc powder and urea in a mortar, and grinding in a room temperature environment; (2) putting the ground mixture into a porcelain boat, heating to 500-600 DEG C in a tubular furnace, and preserving heat; (3) collecting the naturally cooled product, so as to obtain a product h-g-C3N4; the metal zinc negative electrode protective layer of the aqueous zinc ion battery prepared by the invention is of a unique porous structure with a high specific surface area, can balance electric field distribution, induce uniform electrolyte flux, guide zinc ions to uniformly deposit and inhibit dendritic crystal growth, and meanwhile, avoids the consequence of battery short circuit caused by the fact that zinc dendritic crystals pierce a diaphragm; the cycling stability and the electrochemical performance of the battery are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage, and specifically relates to a preparation method and application of a metallic zinc negative electrode protective layer of an aqueous zinc ion battery. Background Art

[0002] As the energy crisis intensifies and environmental pollution worsens, the demand for clean energy to replace traditional energy is becoming increasingly urgent. In recent years, the rise of new energy electric vehicles and portable electronic products has accelerated the development of clean and sustainable energy. Although lithium-ion batteries have been commercialized due to their high energy density, their limited resources, high cost and low safety have prompted people to urgently find alternatives.

[0003] Zinc-ion batteries have high safety, environmental friendliness and high theoretical capacity (820 mAh / g, 5855 mAh / cm 3 ), showing great potential in the new generation of large-scale energy storage systems. In addition, the use of aqueous electrolytes gives zinc-ion batteries higher ionic conductivity and rate performance. However, during the charge and discharge process, zinc ions are unevenly deposited on the surface of the zinc negative electrode, which easily forms dendrites, consumes a large amount of active materials, reduces coulombic efficiency, and may even pierce the diaphragm and cause a short circuit. The hydrogen generated by the hydrogen evolution reaction will also increase the internal pressure, causing battery expansion and electrolyte leakage. These problems have hindered the commercialization of aqueous zinc-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, provide a method for preparing a protective layer of a metallic zinc negative electrode of an aqueous zinc ion battery, solve the problem of dendrite growth of the zinc negative electrode, and extend the cycle life of the battery.

[0005] The present invention adopts the following technical solutions: A method for preparing a metallic zinc negative electrode protective layer of an aqueous zinc ion battery comprises the following steps: (1) A certain amount of zinc powder and urea are mixed in a mortar and ground at room temperature; (2) placing the ground mixture into a porcelain boat, heating it to 500-600° C. at a certain heating rate in a tube furnace and keeping it warm for a period of time; (3) Collecting the product after natural cooling to obtain the product hg-C3N4 material, which can be used as a protective layer for the metal zinc negative electrode of an aqueous zinc ion battery.

[0006] Furthermore, in step (1), the mass ratio of zinc powder to urea is 7:100.

[0007] Furthermore, in step (2), the heating rate of the tubular furnace is 3 to 5 °C / min, and the holding time is 1 to 3 h.

[0008] Furthermore, in step (3), the cooling rate of the tubular furnace is natural cooling.

[0009] The present invention also provides a protective layer for a metallic zinc negative electrode of an aqueous zinc ion battery, which is prepared by the above-mentioned preparation method.

[0010] The present invention also provides a pole piece, which is obtained by ultrasonically coating the above-mentioned material on zinc foil and vacuum drying, and is recorded as hg-C3N4@Zn pole piece.

[0011] Furthermore, the vacuum drying temperature is 60-80°C, the drying time is 8-12 h, and the material coating method adopts an ultrasonic method.

[0012] The present invention also provides an application of an electrode sheet in the preparation of an aqueous zinc ion battery, wherein the electrolyte used in the aqueous zinc ion battery is a 2 mol / L ZnSO4 solution.

[0013] The beneficial effects of the present invention are as follows: 1. The present invention provides a method for preparing a protective layer of a metallic zinc negative electrode of an aqueous zinc ion battery. The preparation method is scientifically and reasonably designed, only requires one step of high-temperature calcination, and has a simple process. It has great application prospects in the practical application of zinc ion batteries.

[0014] 2. The protective layer of the metallic zinc negative electrode of the aqueous zinc ion battery prepared by the present invention is a unique porous structure with a high specific surface area. This structure can balance the electric field distribution, induce uniform electrolyte flux, and guide the uniform deposition of zinc ions, thereby achieving the purpose of inhibiting dendrite growth. At the same time, it avoids the consequences of zinc dendrites piercing the diaphragm and causing battery short circuit, greatly improving the cycle stability and electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the XRD pattern of hg-C3N4 material.

[0016] Figure 2 This is the SEM image of hg-C3N4 material.

[0017] Figure 3 SEM and EDS images of hg-C3N4 materials.

[0018] Figure 4 This is a physical picture of whg-C3N4 and hg-C3N4 materials (the bottle marked g-C3N4 on the left in the picture is whg-C3N4).

[0019] Figure 5 The zinc electrode sheets in Example 1 and Example 3 were assembled into 1 mA cm -2 - 1 mAh cm -2Long cycle curve of a symmetric battery.

[0020] Figure 6 The zinc electrode sheets in Example 1 and Example 2 were assembled into 1 mA cm -2 - 1 mAh cm -2 Long cycle curve of a symmetric battery.

[0021] Figure 7 The zinc electrode sheets and MnO2 in Examples 1 and 3 are assembled into 1A g -1 Long cycle curve of the full battery.

[0022] Figure 8 The zinc electrode sheets and MnO2 in Examples 1 and 2 are assembled into 1A g -1 Long cycle curve of the full battery.

[0023] Fig. 9 It is the rate diagram of the symmetrical battery of zinc electrode sheets in Example 1 and Example 3.

[0024] Fig.10 It is the rate diagram of the symmetrical battery of zinc electrode sheets in Example 1 and Example 2.

[0025] Fig.11 This is a rate diagram of the zinc electrode sheet and MnO2 assembled into a full battery in Example 1 and Example 3.

[0026] Fig.12 This is a SEM image of the surface of the full battery assembled with the zinc electrode sheet and MnO2 in Example 1 after 50 cycles.

[0027] Fig.13 This is a SEM image of the surface of the full battery assembled with the zinc electrode sheet and MnO2 in Example 3 after 50 cycles.

[0028] Fig.14 The zinc electrode sheets and MnO2 in Examples 1 and 3 are assembled into 0.2A g -1 Long cycle curve of the full battery.

[0029] Fig.15 The zinc electrode sheets and MnO2 in Example 1 and Example 2 are assembled into 0.2A g -1 Long cycle curve of the full battery.

[0030] Fig.16 The zinc electrode sheets in Example 1 and Example 3 were assembled into 3 mA cm -2 - 3 mAh cm -2 Long cycle curve of a symmetric battery.

[0031] Fig.17The zinc electrode sheets in Example 1 and Example 2 were assembled into 3 mA cm -2 - 3 mAh cm -2 Long cycle curve of a symmetric battery. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1.

[0034] This embodiment includes the following steps: (1) Preparation of zinc electrode sheet First, pre-treat the zinc sheet (zinc foil). Choose a 1-2mm thick zinc sheet, use sandpaper to smooth one side of the zinc sheet, then rinse it with deionized water 2-4 times, and finally rinse it with ethanol 2-4 times. Dry the zinc foil after the above treatment and set it aside. The above purpose is to remove the oxide layer and surface impurities generated by the zinc foil in the air.

[0035] (2) Assembling the battery The zinc negative electrode material prepared in step (1) is cut into electrode sheets with a diameter of 12 mm by a slicer, and two identical electrode sheets are used as positive and negative electrode sheets respectively. First, the spring sheet and the gasket are placed in the negative electrode shell, and then a zinc negative electrode sheet is placed in the negative electrode shell, ensuring that the smooth side contacts the diaphragm, and then a glass fiber diaphragm is placed, and 6-8 drops of zinc sulfate solution with a concentration of 2 mol / L are dripped as an electrolyte to completely wet the glass fiber diaphragm, and then another zinc negative electrode sheet is placed on top of the diaphragm, and the smooth side is also contacted with the diaphragm, and then the gasket is placed, and finally the positive electrode shell is buckled, and the battery is packaged using a battery packaging machine, that is, an unmodified zinc negative electrode aqueous zinc ion symmetrical button battery is obtained, marked as Zn / / Zn symmetrical button battery (referred to as symmetrical battery). Replace one of the Zn electrode sheets with a MnO2 electrode sheet and assemble it, and you can get an unmodified zinc negative electrode aqueous zinc ion full button battery, marked as Zn / / MnO2 full button battery (referred to as full battery).

[0036] Example 2 This embodiment includes the following steps: (1) Preparation of zinc negative electrode coating material Weigh 10 g of urea and grind it in a mortar for half an hour. Then put it in a tube furnace and heat it to 520 °C at a rate of 5 °C / min in an Ar atmosphere. Keep it warm for 2 hours, then quickly raise the temperature to 550 °C and keep it for 2 hours. After the reaction is completed. After cooling naturally to room temperature, collect the product to obtain the whg-C3N4 coating material, which looks like Figure 4 shown.

[0037] (2) Preparation of zinc electrode sheet with coating material 30 mg of whg-C3N4 and the zinc electrode sheet treated in Example 1 were placed in 100 mL of deionized water at the same time. After 40 min of ultrasonic treatment, the zinc foil was taken out and placed in a vacuum oven and dried at 60 °C for 12 h to obtain a zinc negative electrode material of whg-C3N4@Zn, that is, a whg-C3N4 coating material was attached to the surface of the zinc electrode sheet; the zinc negative electrode material was cut into electrode sheets with a diameter of 12 mm using a slicer.

[0038] (3) Assembling batteries Take two identical zinc electrode sheets as positive and negative electrode sheets respectively, first put the spring sheet and the gasket into the negative electrode shell, then put a zinc negative electrode sheet into the negative electrode shell, ensure that the smooth surface with the coating contacts the diaphragm, then put in the glass fiber diaphragm, drip 6-8 drops of 2mol / L zinc sulfate solution as the electrolyte to make the glass fiber diaphragm completely infiltrated, then put another zinc negative electrode sheet on the top of the diaphragm, also make the coated side contact the diaphragm, then put in the gasket, and finally buckle the positive electrode shell, and use the battery packaging machine to package the battery, that is, a modified zinc negative electrode aqueous zinc ion symmetrical button battery is obtained, marked as whg-C3N4@Zn / / whg-C3N4@Zn symmetrical battery; replace one of the whg-C3N4@Zn electrode sheets with a MnO2 electrode sheet and assemble it, and you can get a modified zinc negative electrode aqueous zinc ion full button battery, marked as whg-C3N4@Zn / / MnO2 full battery.

[0039] Example 3 This embodiment includes the following steps: (1) Preparation of zinc negative electrode coating material Weigh 0.7 g zinc powder and 10 g urea and grind them in a mortar for half an hour. Then put them in a tube furnace and heat them to 520 °C at a rate of 5 °C / min in an Ar atmosphere. Keep the temperature for 2 hours, then quickly raise the temperature to 550 °C and keep it for 2 hours. After the reaction is completed. After cooling naturally to room temperature, collect the product to obtain hg-C3N4 material. Characterize it as follows Figure 1-4As shown, the carbon nitride crystal has a high specific surface area, a porous structure, and a graphite-like phase.

[0040] (2) Preparation of zinc electrode sheet with coating material 30 mg of hg-C3N4 and the zinc electrode sheet treated in Example 1 were placed in 100 mL of deionized water at the same time. After 40 min of ultrasonic treatment, the zinc foil was placed in a vacuum oven and dried at 60 °C for 12 h to obtain a zinc negative electrode material of hg-C3N4@Zn, that is, a hg-C3N4 coating material was attached to the surface of the zinc electrode sheet. The zinc negative electrode material was cut into electrode sheets with a diameter of 12 mm using a slicer.

[0041] (3) Assembling batteries Two identical electrode sheets are selected as positive and negative electrode sheets respectively. First, the spring and gasket are placed in the negative electrode shell, and then a zinc negative electrode sheet is placed in the negative electrode shell, ensuring that the smooth surface with the coating contacts the diaphragm, and then a glass fiber diaphragm is placed, and 6-8 drops of 2mol / L zinc sulfate solution are dripped as an electrolyte to completely soak the glass fiber diaphragm, and then another zinc negative electrode sheet is placed on top of the diaphragm, and the smooth surface with the coating contacts the diaphragm, and then the gasket is placed, and finally the positive electrode shell is buckled, and the battery is packaged using a battery packaging machine, and a modified zinc negative electrode aqueous zinc ion symmetrical button battery is obtained, marked as hg-C3N4@Zn / / hg-C3N4@Zn symmetrical battery; one of the hg-C3N4@Zn electrode sheets is replaced with a MnO2 electrode sheet and assembled, and a modified zinc negative electrode aqueous zinc ion full button battery is obtained, marked as hg-C3N4@Zn / / MnO2 full battery.

[0042] like Figure 5-6 As shown, the cycle performance test was performed on the symmetrical batteries assembled in the above Examples 1-3; Figure 5 In the symmetrical battery in Example 3, because an artificial coating interface is constructed on the surface of the zinc negative electrode to modify it, the coating plays an effective protective role, and there is a small polarization voltage during the battery cycle. At a current density of 1 mA cm -2 , deposition capacity is 1 mAhcm -2 Under the condition, it can cycle for 1000 hours; Figure 6 The symmetrical battery in Example 2 was cycled for only about 500 h, but it was longer than the cycle time of the symmetrical battery in Example 1 without coating protection.

[0043] like Fig.16 As shown, the symmetrical battery in Example 3 has a current density of 3 mA cm -2 , deposition capacity is 3 mAhcm -2Under the same conditions, the negative electrode can be cycled for 270 hours with the polarization voltage remaining almost unchanged, while the unmodified zinc negative electrode can only be cycled for a short time before the voltage fluctuates violently. Fig.17 As shown, at a current density of 3 mA cm -2 , deposition capacity is 3 mAhcm -2 The polarization voltage of Example 1 is almost the same as that of Example 2. The above results show that the surface modified coating of Example 3 can inhibit the growth of dendrites and the occurrence of side reactions, thereby improving the stability and long cycle life of the battery.

[0044] The symmetrical batteries in Example 1, Example 2 and Example 3 were subjected to charge and discharge rate performance tests. The test conditions were as follows: the charge and discharge mode was constant current charging, and the current densities were 0.2, 0.4, 1, 2, 4, and 10 mA cm -2 , then back to 4, 2, 1, 0.4, 0..2 mA cm -2 After 10 cycles, the capacity remained at 1 mAh cm -2 , the rate performance curve is as follows Fig. 9 and Fig.10 As shown. Fig. 9 and Fig.10 It can be seen that the symmetrical cell modified with hg-C3N4 in Example 3 has excellent rate performance. -2 Increased to 10 mA cm -2 When the hg-C3N4-modified zinc anode is subjected to high cycling performance, it remains stable under low voltage polarization.

[0045] like Figure 7-8 , Figure 14-15 As shown, the full batteries prepared in Example 1, Example 2 and Example 3 were subjected to cycle performance tests, the positive electrode material of the full battery was MnO2, and the test conditions were: the charge and discharge mode was constant current charge and discharge, Figure 7 and Figure 8 The conditions shown are: current density 1A g -1 , the charge cut-off voltage is 1.8V, and the discharge cut-off voltage is 0.8V; Fig.14 and Fig.15 The conditions shown are: current density 0.2A g -1 , the charge cut-off voltage is 1.8V, and the discharge cut-off voltage is 0.8V. Figure 7 and Figure 8 It can be seen that the full battery prepared in Example 3 has a -1 At a current density of 1.34 W, the specific capacity after 1300 cycles reached 143.0 mAh g -1 , has good cycle stability performance, and the capacity remains equal to the original capacity. Fig.14 It can be seen that the full battery prepared in Example 3 has a -1 At a current density of 1.34 W, the specific capacity after 80 cycles reached 460.0 mAh g -1 , has good cycle stability performance, and the capacity is higher than the initial capacity.

[0046] like Fig.11 As shown, the rate performance of the full batteries prepared in Examples 1 and 3 was tested under the following test conditions: the charge and discharge mode was constant current charging, and the current density was 0.1, 0.2, 0.5, 1, 2, and 0.1 A g -1 The discharge cut-off voltage is 0.8V and the charge cut-off voltage is 1.8V. The rate performance cycle curve is shown in the figure below. Fig.11 As shown. Fig.11 It can be seen that the battery modified with hg-C3N4 prepared in Example 3 has a high current density of 0.1, 0.2, 0.5, 1, 2, and 0.1 A g -1 The specific capacities are all higher than those of the full battery assembled with the unmodified bare zinc negative electrode, and Example 3 exhibits excellent rate performance.

[0047] like Figure 12-13 As shown, we also cycled the full battery assembled with zinc electrode sheets and MnO2 in Examples 1 and 3 for 50 cycles, and then performed SEM tests on the surface of the zinc electrode sheets. The results are as follows: Figure 12-13 , Fig.12 The surface of the bare zinc electrode sheet in Example 1 without modification is covered with zinc dendrites, while Fig.12 It shows that the zinc electrode protected by the hg-C3N4 modified coating is still flat and smooth, which indicates that the hg-C3N4 coating material obviously plays a role in inhibiting the growth of dendrites.

Claims

1. A method for preparing a metal zinc negative electrode protective layer material for an aqueous zinc ion battery, characterized in that: The steps include: (1) A certain amount of zinc powder and urea were mixed in a mortar and ground at room temperature; (2) placing the ground mixture into a tube furnace, heating it to 500-600° C. at a certain heating rate under an Ar atmosphere and keeping it at this temperature for a period of time; (3) Collecting the product after natural cooling to obtain the product hg-C3N4 material, which can be used as a protective layer material for the metal zinc negative electrode of an aqueous zinc ion battery.

2. The method for preparing a metal zinc negative electrode protective layer material for an aqueous zinc ion battery according to claim 1, wherein: In step (1), the mass ratio of zinc powder to urea is 7:

100.

3. The method for preparing a metal zinc negative electrode protective layer material for an aqueous zinc ion battery according to claim 1, characterized in that: In step (2), the heating rate of the tubular furnace is 3 to 5 °C / min, and the holding time is 1 to 3 h.

4. A metal zinc negative electrode sheet for an aqueous zinc ion battery with a protective layer, characterized in that: The protective layer material prepared by any one of claims 1 to 3 is coated on a zinc sheet by a certain coating method and is recorded as hg-C3N4@Zn electrode.

5. The aqueous zinc ion battery metal zinc negative electrode sheet with a protective layer according to claim 4, characterized in that: The coating method is as follows: firstly, the zinc sheet is polished to be smooth, a certain amount of protective layer material and the zinc sheet are simultaneously put into deionized water, ultrasonically treated for a certain time, and then the zinc sheet is taken out and vacuum dried for a certain time.

6. Use of the aqueous zinc ion battery metal zinc negative electrode sheet with a protective layer as claimed in claim 5 in an aqueous zinc ion battery.